CAGE22-2 Scientific Cruise Report: AKMA 2/Ocean Senses - Panieri, Giuliana; Bünz, Stefan; Savini, Alessandra; Jensen, Andre; Løfquist, Bjørn; Olsen, Bjørn Runar; Willis, Ciara; Argentino, Claudio; Bertin, Clément; Oddone, Davide; Kalenitchenko, Dimitri; Rosnes, Erling; et al. (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
AKMA-OceanSenses Research Expedition (11-23 May 2022) aboard the research vessel Kronprins Håkon to the Barents Sea and Arctic Ocean is focused on both science and education. This expedition has received endorsement from the UN Ocean Decade. The cruise may be known as: CAGE22_2